ANALISIS FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - YOHANES YOHANES; FIELICIA KARNADI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research aims to examine whether there is an effect of firm size, firm age, profitability, leverage, sales growth and institutional ownership on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange. This research used 61 manufacturing companies listed on the Indonesia Stock Exchange during the period 2017 to 2019 which were taken using a purposive sampling method in order to obtain 183 company data and then will be used for sample in this research. In addition, the research data were analyzed using multiple linear regression models and then will be tested to examine are there an effect of each variable on tax avoidance, The empirical results of this research indicates that firm size, firm age, leverage, sales growth and institutional ownership have no influence on tax avoidance. However, profitability has influence on tax avoidance. This research is expected to provide an overview to companies in carrying out their operational activities related to behavioral control on tax avoidance activities. In addition, this research is expected to be used as information, knowledge and as a comparison in conducting research. The difference between this study and the previous one is the addition of institutional ownership variables and observation periods within a period of 3 years, from 2017 to 2019